ANALISIS PEMBELAJARAN PENDIDIDKAN PANCASILA DAN KEWARGANEGARAAN DAN PENANAMAN KARAKTER SISWA DI MTs MA’ARIF NU 2 SUTOJAYAN - Binti Lailatul Faizah; Minto Santoso; Arik Cahyani (SILABUS: Jurnal Ilmu dan Inovasi Pendidikan, 2024)
Learning is a combination of two activities, learning and teaching. Methodological learning activities tend to be more dominant among students, while instructional teaching is carried out by teachers. So, the term learning is a summary of the words learning and teaching. Learning is usually provided by educators so that the process of acquiring knowledge and knowledge, mastering skills and habits, as well as forming attitudes and beliefs in students can occur. In other words, learning is a process to help students learn well. Pancasila and Citizenship Education (PPKn) is an important component of learning in schools, both formal and informal schools. We can see this from the existence of PPKn subjects at various levels of education, from elementary school (SD), junior high school (SMP). High School (SMA) or college. In accordance with the opening words of the 1945 Constitution, "to make the life of the nation intelligent" which is the ideal of the Indonesian nation, is one of the drivers that Pancasila and Citizenship Education is very important in learning. Pancasila and citizenship education is an important part of the education curriculum in Indonesia. MTs Ma'arif NU 2 Sutojayan integrates Pancasila and citizenship learning into existing subjects. This learning aims to teach the basic values ​​of Pancasila, the rights and obligations of citizens, as well as knowledge about the Indonesian government system. The importance of learning Pancasila and citizenship education is to form citizens who have a good understanding of their duties and responsibilities in society and government.